Acolhimento de refugiados: alimentação e necessidades nutricionais em situações de emergência - Valdiviesso, R. (2015)
Europe is now a major destination of an intense migratory flow caused by armed conflicts in the Middle East and Africa. In this sense, the European Commission (EC) agreed on the distribution of some of these people in clear need of international protection by various Member States. The populations in transit and the characteristics of its reception have specificities that can compromise the access to adequate food and basic health care. They can also influence morbidity and mortality in affected groups. This manual aims to establish a framework of nutrition and food intervention to refugees in Portugal. It is aimed at all those who support it, either individually or institutionally, and are responsible for any aspect related to the health and nutrition of these populations, facilitating the implementation of care and providing tools for decision making. The manual is organized into 3 parts. It begins with the assessment of nutritional status of the population. Then presents several strategies to support the design of food and nutrition intervention based on the estimated nutritional needs for these population groups. In the final section it addresses the importance of ensuring food safety and hygiene when providing this food assistance. This manual also addresses some considerations towards basic psychological intervention principles, destined to help the teams on the field.